Draft Annual Plan (2011-2012) Part-III (Statements) Government of Tripura - Planning Commission (Planning Commission, 2011)
Sector wise Draft Annual Plan 2011-12 Proposed Outlays, Draft Annual Plan 2011-12 Proposed Outlays (Scheme-wise), Physical Targets and Achievements, Statement Regarding EAP, Bharat Nirman Programmes, Centrally Sponsored Schemes, Draft Annual Plan 2011-12 Financial Outlays : Proposals for TSP, Draft Annual Plan 2011-12 Physical Targets and Achievements : Proposals for TSP, Draft Annual Plan 2011-12 Financial Outlays : Proposals for SCSP, Draft Annual Plan 2011-12 Physical Targets and Achievements : Proposals for SCSP, Draft Annual Plan 2011-12 Financial Outlays / expenditure : Proposals for Voluntary Sector.
Planning (P and C) Department, Government of Tripura
Planning (P and C) Department, Government of Tripura